Hot rolled steel plate
By optimizing the chemical composition and metal structure of hot-rolled steel plates, combining martensite, bainite and ferrite, controlling the Mn concentration and metal structure uniformity, the problem of difficulty in taking into account high strength and excellent formability in the prior art is solved. , achieves hot-rolled steel plates with high strength, ductility and shear processing properties.
Patent Information
- Application Number
- CN202180051745.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-27
- Filing Date
- 2021-06-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-06-15
AI Technical Summary
The prior art is difficult to take into account high strength, excellent ductility and shear processing properties, especially in automotive components, it is difficult to meet the high strength requirements of 980 MPa or above while maintaining good formability.
By optimizing the chemical composition and metal structure of the hot-rolled steel sheet, an appropriate amount of martensite or bainite is contained to increase strength and ferrite is combined to enhance ductility. At the same time, by controlling the standard deviation of Mn concentration and the uniformity of metal structure, the occurrence of secondary shear surfaces is suppressed, thereby improving shear processing properties.
It realizes high strength (tensile strength of 980MPa or above), excellent ductility and shear processing properties of hot-rolled steel plates, and is suitable for automotive components and other mechanical structures.
Smart Images

Figure BDA0004089674520000151 
Figure BDA0004089674520000152 
Figure BDA0004089674520000251
Abstract
Description
Technical Field
[0001] The present invention relates to a hot-rolled steel sheet, and more specifically to a hot-rolled steel sheet that can be formed into various shapes by press working or the like and is particularly related to a hot-rolled steel sheet that has high strength and excellent ductility and shear workability.
[0002] This application claims priority based on Japanese Patent Application No. 2020-143742 filed on August 27, 2020, the contents of which are cited here. Background Art
[0003] In recent years, from the perspective of protecting the global environment, many fields are trying to reduce carbon dioxide emissions. Even automobile manufacturers are actively developing technologies to reduce vehicle weight for the purpose of reducing fuel consumption. However, in order to ensure the safety of passengers, the focus is also placed on improving collision resistance, so reducing the weight of the vehicle body is not easy.
[0004] In order to balance the lightweight of the vehicle body with the collision resistance, the use of high-strength steel plates to make the components thinner is being studied. Therefore, there is an urgent need for steel plates that have both high strength and excellent formability, and several technologies have been proposed in the past to meet these requirements. Since automobile components have a variety of processing methods, the required formability varies depending on the components used, but ductility is listed as an important indicator of formability. In addition, automobile components are formed by press forming, but most of the press-formed slabs are manufactured by shearing with high productivity. The slabs manufactured by shearing require excellent end face accuracy after shearing. For example, if the appearance of the end face after shearing (shear end face) has a secondary shear surface such as shear surface-fracture surface-shear surface, the accuracy of the shear end face will be significantly deteriorated.
[0005] Regarding the technology for improving ductility, for example, Patent Document 1 discloses a high-strength steel sheet for automobiles having excellent collision safety and formability, in which retained austenite having an average grain size of 5 μm or less is dispersed in ferrite having an average grain size of 10 μm or less. In a steel sheet having a metal structure containing retained austenite, although austenite undergoes a martensitic transformation during processing and exhibits a large elongation due to transformation-induced plasticity, the hole expandability is impaired due to the formation of hard martensite. Patent Document 1 also discloses that by refining ferrite and retained austenite, not only ductility but also hole expandability can be improved.
[0006] Patent Document 2 discloses a high-strength steel sheet having a tensile strength of 980 MPa or more, in which a second phase composed of retained austenite and / or martensite is finely dispersed in grains and which has excellent ductility and stretch flangeability.
[0007] Regarding the technology for improving shear workability, for example, Patent Document 3 discloses a method of increasing the ferrite grain size d of the surface layer by s and the internal ferrite grains d b The ratio d s / d b The technology of controlling the burr height after punching by controlling it below 0.95.
[0008] Patent Document 4 discloses a technique for improving peeling and curling of the sheet end surface by reducing the P content.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Laid-Open No. 11-61326
[0012] Patent Document 2: Japanese Patent Application Publication No. 2005-179703
[0013] Patent Document 3: Japanese Patent Application Laid-Open No. 10-168544
[0014] Patent Document 4: Japanese Patent Application Publication No. 2005-298924
[0015] Non-patent literature
[0016] Non-patent document 1: J. Webel, J. Gola, D. Britz, F. Mucklich, Materials Characterization 144 (2018) 584-596
[0017] Non-patent literature 2: DL Naik, HU Sajid, R. Kiran, Metals 2019, 9, 546
[0018] Non-patent document 3: K. Zuiderveld, Contrast Limited Adaptive Histogram Equalization, Chapter VIII.5, Graphics Gems IV. P. S. Heckbert (Eds.), Cambridge, MA, Academic Press, 1994, pp. 474-485 Summary of the invention
[0019] Problems to be solved by the invention
[0020] The technologies disclosed in Patent Documents 1 to 4 are all technologies for improving either ductility or the end surface properties after shearing. However, Patent Documents 1 to 3 do not mention technologies that take these properties into consideration. Patent Document 4 does not mention taking shearing workability and press formability into consideration. However, the steel plate disclosed in Patent Document 4 has a strength of less than 850 MPa, and therefore is sometimes difficult to use for high-strength components of 980 MPa or more.
[0021] The present invention has been made in view of the above-mentioned problems in the prior art, and an object of the present invention is to provide a hot-rolled steel sheet having high strength and excellent ductility and shear workability.
[0022] Means for solving problems
[0023] In view of the above problems, the inventors have repeatedly conducted intensive research on the chemical composition of hot-rolled steel sheets, the relationship between metal structure and mechanical properties, and obtained the following insights (a) to (i), thereby completing the present invention. In addition, the term "excellent shear workability" means that the generation of secondary shear surfaces can be suppressed during shearing. In addition, the term "excellent strength" or "high strength" means that the tensile strength is 980 MPa or more.
[0024] (a) In order to obtain excellent tensile (maximum) strength, it is preferable to use a hard structure. In other words, it is preferable that the metal structure contains martensite or bainite.
[0025] (b) However, since hard structures are structures lacking in ductility, excellent ductility cannot be ensured simply by forming a metal structure mainly composed of these.
[0026] (c) In order to achieve both high-strength hot-rolled steel sheets and excellent ductility, it is effective to contain an appropriate amount of ferrite having high ductility.
[0027] (d) Since ferrite is generally soft, it is necessary to use Ti, Nb, V, etc. as precipitation strengthening elements to obtain the desired strength. Therefore, it is effective to obtain an appropriate amount of precipitation strengthening ferrite by performing intermediate air cooling during the hot rolling process.
[0028] (e) To suppress the occurrence of secondary shear planes, it is important to form a fracture surface after the shear plane is fully formed. To this end, it is necessary to suppress the early occurrence of cracks from the tool tip during shearing. Therefore, it is important to have less Mn segregation, random organization morphology without periodicity, and high uniformity of the metal structure.
[0029] (f) Specifically, keeping the standard deviation of the Mn concentration below a certain value and controlling the periodicity and uniformity of the metal structure are effective in suppressing the secondary shear plane.
[0030] (g) In order to make the standard deviation of Mn concentration below a certain value, the slab heating process and the subsequent hot rolling process are important. For example, it is effective to perform hot rolling in a manner that the slab is kept in a temperature range of 700 to 850°C for more than 900 seconds before heating, kept in a temperature range of 1100°C or more for more than 6000 seconds, and reduced the thickness of the slab by more than 90% in total in a temperature range of 850°C to 1100°C.
[0031] (h) It is important to control the recrystallization behavior of austenite during hot rolling to reduce the periodicity of the microstructure. For example, it is effective to control the reduction rate and rolling temperature in the final stage of hot rolling within a specified range, set the stress applied to the steel plate after the first stage of hot rolling and before the final stage of rolling to 170 kPa or more, and set the stress applied to the steel plate after the final stage of hot rolling and until the steel plate is cooled to 800°C to less than 200 kPa. According to such hot rolling conditions, fine and equiaxed recrystallized austenite grains can be implanted, and by combining with the subsequent cooling conditions, the periodicity of the microstructure can be reduced.
[0032] (i) An effective method for improving the uniformity of the metal structure is to obtain a desired amount of ferrite by performing intermediate air cooling and then suppress the precipitation of iron carbides by cooling to 350° C. or less.
[0033] The gist of the present invention completed based on the above findings is as follows.
[0034] (1) One aspect of the present invention relates to a hot-rolled steel sheet, characterized in that:
[0035] The chemical composition contains by mass %:
[0036] C: 0.050~0.250%,
[0037] Si: 0.05-3.00%,
[0038] Mn: 1.00~4.00%,
[0039] One or more of Ti, Nb and V: 0.060 to 0.500% in total,
[0040] Sol.Al: 0.001~2.000%,
[0041] P: 0.100% or less,
[0042] S: 0.0300% or less,
[0043] N: 0.1000% or less,
[0044] O: 0.0100% or less,
[0045] Cu: 0-2.00%,
[0046] Cr: 0~2.00%,
[0047] Mo: 0-1.00%,
[0048] Ni: 0-2.00%,
[0049] B: 0~0.0100%,
[0050] Ca: 0~0.0200%,
[0051] Mg: 0~0.0200%,
[0052] REM: 0~0.1000%、
[0053] Bi: 0~0.020%,
[0054] One or more of Zr, Co, Zn and W: 0 to 1.00% in total, and
[0055] Sn: 0~0.05%,
[0056] The remainder includes Fe and impurities;
[0057] The metal structure is expressed in area % as follows:
[0058] The retained austenite is less than 3.0%, the ferrite is 15.0% or more and less than 60.0%, and the pearlite is less than 5.0%;
[0059] The E value representing the periodicity of the metal structure is greater than 10.7, and the I value representing the uniformity of the metal structure is greater than 1.020;
[0060] The standard deviation of the Mn concentration is 0.60 mass % or less;
[0061] The tensile strength is above 980 MPa.
[0062] (2) The hot-rolled steel sheet according to (1) above, wherein the average grain size of the surface layer may be less than 3.0 μm.
[0063] (3) The hot-rolled steel sheet according to (1) or (2) above, wherein the chemical composition may contain, in terms of mass %, one or more elements selected from the following:
[0064] Cu: 0.01-2.00%,
[0065] Cr: 0.01~2.00%,
[0066] Mo: 0.01~1.00%,
[0067] Ni: 0.02-2.00%,
[0068] B: 0.0001~0.0100%,
[0069] Ca: 0.0005~0.0200%,
[0070] Mg: 0.0005~0.0200%,
[0071] REM: 0.0005~0.1000%, and
[0072] Bi: 0.0005~0.020%.
[0073] Effects of the Invention
[0074] According to the above embodiment of the present invention, a hot rolled steel sheet having excellent strength, ductility and shear workability can be obtained. In addition, according to the above preferred embodiment of the present invention, a hot rolled steel sheet having the above characteristics and further suppressing the occurrence of bending internal cracks, i.e., excellent bending internal crack resistance can be obtained.
[0075] The hot-rolled steel sheet according to the above aspect of the present invention is suitable as an industrial raw material for automobile components, mechanical structural parts and building components. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] Figure 1 This is an example of the sheared end surface of the hot-rolled steel sheet according to the example of the present invention.
[0077] Figure 2 This is an example of a sheared end surface of a hot-rolled steel sheet according to a comparative example. DETAILED DESCRIPTION
[0078] The chemical composition and metal structure of the hot-rolled steel sheet (hereinafter sometimes simply referred to as steel sheet) involved in this embodiment are specifically described below. However, the present invention is not limited to the configuration disclosed in this embodiment, and various changes can be made within the scope of the purpose of the present invention.
[0079] In the following numerical ranges between "-", the lower limit and the upper limit are included in the range. In the numerical values expressed as "lower than" or "exceed", the value is not included in the numerical range. In the following description, the % of the chemical composition of the steel plate is mass % unless otherwise specified.
[0080] 1. Chemical composition
[0081] The hot-rolled steel sheet according to the present embodiment contains, by mass%, C: 0.050-0.250%, Si: 0.05-3.00%, Mn: 1.00-4.00%, one or more of Ti, Nb and V: 0.060-0.500% in total, sol.Al: 0.001-2.000%, P: 0.100% or less, S: 0.0300% or less, N: 0.1000% or less, O: 0.0100% or less, and the remainder: Fe and impurities. Each element is described in detail below.
[0082] (1-1) C: 0.050~0.250%
[0083] C can increase the fraction of hard phases, and can increase the strength of ferrite by combining with precipitation strengthening elements such as Ti, Nb, and V. If the C content is less than 0.050%, it is difficult to obtain the desired strength. Therefore, the C content is set to 0.050% or more. The C content is preferably 0.060% or more, more preferably 0.070% or more, and further preferably 0.080% or more.
[0084] On the other hand, if the C content exceeds 0.250%, the ductility of the hot-rolled steel sheet decreases due to a decrease in the fraction of ferrite. Therefore, the C content is set to 0.250% or less. The C content is preferably 0.150% or less.
[0085] (1-2) Si: 0.05-3.00%
[0086] Si has the effect of improving the ductility of hot-rolled steel sheets by promoting the formation of ferrite and the effect of improving the strength of hot-rolled steel sheets by solid solution strengthening of ferrite. In addition, Si has the effect of making steel sound by deoxidation (suppressing the formation of defects such as pores in steel). If the Si content is less than 0.05%, the above effects cannot be obtained. Therefore, the Si content is set to 0.05% or more. The Si content is preferably 0.50% or more, and more preferably 0.80% or more.
[0087] However, if the Si content exceeds 3.00%, the surface properties, chemical conversion treatment properties, ductility and weldability of the steel sheet are significantly deteriorated, and the A3 transformation point is significantly increased. As a result, it is difficult to perform hot rolling stably. Therefore, the Si content is set to 3.00% or less. The Si content is preferably 2.70% or less, and more preferably 2.50% or less.
[0088] (1-3) Mn: 1.00~4.00%
[0089] Mn has the effect of increasing the strength of hot-rolled steel sheets by inhibiting ferrite transformation. If the Mn content is less than 1.00%, a tensile strength of 980 MPa or more cannot be obtained. Therefore, the Mn content is set to 1.00% or more. The Mn content is preferably 1.30% or more, and more preferably 1.50% or more.
[0090] On the other hand, if the Mn content exceeds 4.00%, the hard phase becomes a periodic band due to the segregation of Mn, and it is difficult to obtain the desired shear workability. Therefore, the Mn content is set to 4.00% or less. The Mn content is preferably 3.70% or less, and more preferably 3.50% or less.
[0091] (1-4) One or more of Ti, Nb and V: 0.060 to 0.500% in total
[0092] Ti, Nb and V are elements that precipitate finely in steel as carbides and nitrides, and improve the strength of steel through precipitation strengthening. If the total content of Ti, Nb and V is less than 0.060%, these effects cannot be obtained. Therefore, the total content of Ti, Nb and V is set to 0.060% or more. Furthermore, it is not necessary to contain all of Ti, Nb and V, and any one of them may be contained, and the total content may be 0.060% or more. The total content of Ti, Nb and V is preferably 0.080% or more, and more preferably 0.100% or more.
[0093] On the other hand, if the total content of Ti, Nb and V exceeds 0.500%, workability deteriorates. Therefore, the total content of Ti, Nb and V is set to 0.500% or less, preferably 0.300% or less, more preferably 0.250% or less, and further preferably 0.200% or less.
[0094] (1-5)sol.Al: 0.001~2.000%
[0095] Al, like Si, has the function of improving steel health by deoxidizing it, and also has the function of promoting the formation of ferrite and improving the ductility of hot-rolled steel sheets. If the sol.Al content is less than 0.001%, the above effects cannot be obtained. Therefore, the sol.Al content is set to 0.001% or more. The sol.Al content is preferably 0.010% or more.
[0096] On the other hand, if the sol.Al content exceeds 2.000%, the above effect is saturated and it is not economically preferable, so the sol.Al content is set to 2.000% or less. The sol.Al content is preferably 1.500% or less, more preferably 1.300% or less, and further preferably 1.000% or less.
[0097] In addition, the term "sol.Al" means acid-soluble Al, and refers to solid-solution Al existing in the steel in a solid-solution state.
[0098] (1-6) P: 0.100% or less
[0099] P is an element usually contained as an impurity, but it is also an element that has the effect of improving the strength of hot-rolled steel sheets by solid solution strengthening. Therefore, P can also be actively contained, but P is an element that is easy to segregate. If the P content exceeds 0.100%, the ductility caused by grain boundary segregation decreases significantly. Therefore, the P content is limited to less than 0.100%. The P content is preferably less than 0.030%. The lower limit of the P content does not need to be specifically stipulated, but from the perspective of refining cost, it is preferably set to 0.001%.
[0100] (1-7) S: 0.0300% or less
[0101] S is an element contained as an impurity, and forms sulfide-based inclusions in steel, thereby reducing the ductility of the hot-rolled steel sheet. If the S content exceeds 0.0300%, the ductility of the hot-rolled steel sheet is significantly reduced. Therefore, the S content is limited to 0.0300% or less. The S content is preferably 0.0050% or less. The lower limit of the S content does not need to be particularly specified, but from the viewpoint of refining cost, it is preferably set to 0.0001%.
[0102] (1-8) N: 0.1000% or less
[0103] N is an element contained in steel as an impurity, and has the effect of reducing the ductility of the steel plate. If the N content exceeds 0.1000%, the ductility of the hot-rolled steel plate will decrease significantly. Therefore, the N content is set to 0.1000% or less. The N content is preferably less than 0.0800%, more preferably less than 0.0700%, and further preferably less than 0.0100%. The lower limit of the N content does not need to be specifically specified, but in the case of further refining the metal structure by containing one or more of Ti, Nb and V, in order to promote the precipitation of carbonitrides, the N content is preferably set to 0.0010% or more, and more preferably set to 0.0020% or more.
[0104] (1-9) O: 0.0100% or less
[0105] If O is contained in a large amount in steel, it forms coarse oxides that serve as fracture starting points, causing brittle fracture or hydrogen cracking. Therefore, the O content is set to 0.0100% or less. The O content is preferably 0.0080% or less, and more preferably 0.0050% or less. In order to disperse more fine oxides during deoxidation of molten steel, the O content may be set to 0.0005% or more or 0.0010% or more.
[0106] The remainder of the chemical composition of the hot-rolled steel sheet involved in this embodiment may also be Fe and impurities. In this embodiment, the so-called impurities refer to impurities mixed from the ore and scrap steel materials used as raw materials or the manufacturing environment, etc. and / or impurities allowed within the range that do not have an adverse effect on the hot-rolled steel sheet involved in this embodiment.
[0107] The hot-rolled steel sheet according to the present embodiment may also contain Cu, Cr, Mo, Ni, B, Ca, Mg, REM, Bi, Zr, Co, Zn, W and Sn as arbitrary elements instead of a part of Fe. The lower limit of the content when the above arbitrary elements are not contained is 0%. The above arbitrary elements are described in detail below.
[0108] (1-10)Cu: 0.01~2.00%, Cr: 0.01~2.00%, Mo: 0.01~1.00%, Ni: 0.02~2.00% and B: 0.0001~0.0100%
[0109] Cu, Cr, Mo, Ni and B all have the effect of improving the hardenability of hot-rolled steel sheets. In addition, Cu and Mo have the effect of improving the strength of hot-rolled steel sheets by precipitating as carbides in steel. In addition, Ni has the effect of effectively suppressing the grain boundary cracks of the slab caused by Cu when Cu is contained. Therefore, one or more of these elements may also be contained.
[0110] Cu has the effect of improving the hardenability of hot-rolled steel sheets and the effect of improving the strength of hot-rolled steel sheets by precipitating carbides in steel at low temperatures. In order to more reliably obtain the above-mentioned effects, it is preferred that the Cu content be set to 0.01% or more, and more preferably to 0.05% or more. However, if the Cu content exceeds 2.00%, grain boundary cracks sometimes occur in the slab. Therefore, the Cu content is set to 2.00% or less. The Cu content is preferably 1.50% or less, and more preferably 1.00% or less.
[0111] As mentioned above, Cr has the effect of improving the hardenability of hot-rolled steel sheets. In order to more reliably obtain the above-mentioned effect, it is preferred that the Cr content be set to 0.01% or more, and more preferably to 0.05% or more. However, if the Cr content exceeds 2.00%, the chemical conversion treatability of the hot-rolled steel sheet is significantly reduced. Therefore, the Cr content is set to 2.00% or less.
[0112] As mentioned above, Mo has the effect of improving the hardenability of hot-rolled steel sheets and the effect of improving the strength of hot-rolled steel sheets by precipitating carbides in steel. In order to more reliably obtain the effects of the above effects, it is preferred that the Mo content be set to 0.01% or more, and more preferably to 0.02% or more. However, even if the Mo content is set to more than 1.00%, the effects of the above effects are saturated, which is not economically preferred. Therefore, the Mo content is set to 1.00% or less. The Mo content is preferably 0.50% or less, and more preferably 0.20% or less.
[0113] As mentioned above, Ni has the effect of improving the hardenability of hot-rolled steel sheets. In addition, Ni has the effect of effectively suppressing the grain boundary cracks of the slab caused by Cu when Cu is contained. In order to more reliably obtain the effect of the above-mentioned effect, it is preferred to set the Ni content to 0.02% or more. Since Ni is a high-priced element, it is not economically preferable to contain a large amount of Ni. Therefore, the Ni content is set to 2.00% or less.
[0114] As mentioned above, B has the effect of improving the hardenability of hot-rolled steel sheets. In order to more reliably obtain the effect of this effect, it is preferred that the B content be set to 0.0001% or more, and more preferably to 0.0002% or more. However, if the B content exceeds 0.0100%, the formability of the hot-rolled steel sheet is significantly reduced, so the B content is set to 0.0100% or less. It is preferred that the B content be set to 0.0050% or less.
[0115] (1-11) Ca: 0.0005 to 0.0200%, Mg: 0.0005 to 0.0200%, REM: 0.0005 to 0.1000%, and Bi: 0.0005 to 0.020%
[0116] Ca, Mg and REM all have the effect of improving the ductility of hot-rolled steel sheets by adjusting the shape of inclusions in steel to a preferred shape. In addition, Bi has the effect of improving the ductility of hot-rolled steel sheets by refining the solidification structure. Therefore, one or more of these elements may also be contained. In order to more reliably obtain the effects of the above-mentioned effects, it is preferred to set any one or more of Ca, Mg, REM and Bi to 0.0005% or more. However, if the Ca content or the Mg content exceeds 0.0200%, or the REM content exceeds 0.1000%, inclusions are excessively generated in the steel, which sometimes reduces the ductility of the hot-rolled steel sheet. In addition, even if the Bi content exceeds 0.020%, the effect of the above-mentioned effects is saturated, which is not economically preferred. Therefore, the Ca content and the Mg content are set to less than 0.0200%, the REM content is set to less than 0.1000%, and the Bi content is set to less than 0.020%. The Bi content is preferably less than 0.010%.
[0117] Here, REM refers to a total of 17 elements including Sc, Y and lanthanoid elements, and the above REM content refers to the total content of these elements. In the case of lanthanoid elements, they are added in the form of mixed rare earth in industry.
[0118] (1-12) One or more of Zr, Co, Zn and W: 0 to 1.00% in total and Sn: 0 to 0.05%
[0119] Regarding Zr, Co, Zn and W, the present inventors have confirmed that even if these elements are contained in a total amount of 1.00% or less, the effect of the hot-rolled steel sheet according to the present embodiment is not impaired. Therefore, one or more of Zr, Co, Zn and W may be contained in a total amount of 1.00% or less.
[0120] The present inventors have also confirmed that even if a small amount of Sn is contained, the effect of the hot-rolled steel sheet according to the present embodiment is not impaired. However, if a large amount of Sn is contained, defects may occur during hot rolling, so the Sn content is set to 0.05% or less.
[0121] The chemical composition of the hot-rolled steel sheet can be measured by ordinary analytical methods. For example, ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry) can be used for measurement. Furthermore, sol.Al can be measured by ICP-AES using the filtrate after the sample is heated and decomposed with acid. C and S can be measured by the combustion-infrared absorption method, N can be measured by the inert gas melting-thermal conductivity method, and O can be measured by the inert gas melting-non-dispersive infrared absorption method.
[0122] 2. Metal structure of hot rolled steel plate
[0123] Next, the metal structure of the hot-rolled steel sheet according to the present embodiment will be described.
[0124] In the hot-rolled steel sheet involved in the present embodiment, the metal structure is calculated by area % as follows: retained austenite is less than 3.0%, ferrite is more than 15.0% and less than 60.0%, and pearlite is less than 5.0%. The E value representing the periodicity of the above-mentioned metal structure is more than 10.7, the I value representing the uniformity of the above-mentioned metal structure is more than 1.020, and the standard deviation of the Mn concentration is less than 0.60 mass %. Therefore, the hot-rolled steel sheet involved in the present embodiment can obtain high strength, excellent ductility and shear workability. Furthermore, in the present embodiment, in the section parallel to the rolling direction, the standard deviation of the structure fraction, E value, I value and Mn concentration in the metal structure at a depth of 1 / 4 of the plate thickness from the surface and in the central position in the plate width direction is specified. The reason is that the metal structure in this position can represent the representative metal structure of the steel plate.
[0125] (2-1) Area fraction of retained austenite: less than 3.0%
[0126] Retained austenite is a metal structure that exists in a face-centered cubic lattice even at room temperature. Retained austenite has the effect of improving the ductility of hot-rolled steel sheets through transformation induced plasticity (TRIP). On the other hand, since retained austenite transforms into high-carbon martensite during shearing, it hinders the occurrence of stable cracks and becomes the cause of the formation of secondary shear planes. If the area fraction of retained austenite is more than 3.0%, the above-mentioned effect becomes obvious, and the shear workability of the hot-rolled steel sheet deteriorates. Therefore, the area fraction of retained austenite is set to less than 3.0%. The area fraction of retained austenite is preferably less than 1.5%, and more preferably less than 1.0%. Since the less retained austenite, the better, the area fraction of retained austenite can also be 0%.
[0127] The area fraction of retained austenite can be measured by X-ray diffraction, EBSP (Electron Back Scattering Diffraction Pattern) analysis, magnetic measurement, etc., and the measured value may differ depending on the measurement method. In the present embodiment, the area fraction of retained austenite is measured by X-ray diffraction.
[0128] In the measurement of the area fraction of retained austenite based on X-ray diffraction in the present embodiment, first, Co-Kα rays are used to determine the cumulative intensity of a total of six peaks, namely, α(110), α(200), α(211), γ(111), γ(200), and γ(220), at a depth of 1 / 4 of the plate thickness (the region from 1 / 8 of the plate thickness from the surface to 3 / 8 of the plate thickness from the surface) of the hot-rolled steel plate and a cross section parallel to the rolling direction at the center position in the plate width direction, and the area fraction of retained austenite is calculated by using the intensity averaging method.
[0129] (2-2) Area fraction of ferrite: 15.0% or more and less than 60.0%
[0130] Ferrite is a structure formed when fcc phase transforms to bcc phase at relatively high temperature. Ferrite has a high work hardening rate, so it has the effect of improving the strength-ductility balance of hot-rolled steel sheet. In order to obtain the above effect, the area fraction of ferrite is set to 15.0% or more, preferably 20.0% or more, more preferably 25.0% or more, and further preferably 30.0% or more.
[0131] On the other hand, since ferrite has low strength, if its area fraction is excessive, desired tensile strength cannot be obtained. Therefore, the ferrite area fraction is set to less than 60.0%, preferably 50.0% or less, and more preferably 45.0% or less.
[0132] (2-3) Area fraction of pearlite: less than 5.0%
[0133] Pearlite is a thin-lamella metal structure in which cementite is precipitated in layers between ferrite, and is a softer metal structure than bainite and martensite. If the area fraction of pearlite is 5.0% or more, the cementite contained in the pearlite consumes carbon, which reduces the strength of the remaining structures, i.e., martensite and bainite, and a tensile strength of 980 MPa or more cannot be obtained. Therefore, the area fraction of pearlite is set to less than 5.0%. The area fraction of pearlite is preferably 3.0% or less. In order to improve the stretch flangeability of the steel plate, it is preferred to reduce the area fraction of pearlite as much as possible, and more preferably the area fraction of pearlite is 0%.
[0134] Furthermore, in the steel plate involved in this embodiment, the remaining structure other than retained austenite, ferrite and pearlite includes a hard structure composed of one or more of bainite, martensite and tempered martensite with a total area fraction exceeding 32.0% and 85.0% or less.
[0135] The area fraction of the metal structure is measured according to the following method. The cross section parallel to the rolling direction is finished into a mirror surface and polished with colloidal silica without alkaline solution at room temperature for 8 minutes to remove the strain introduced into the surface layer of the sample. At any position in the longitudinal direction of the sample cross section, the region with a length of 50 μm and a depth of 1 / 4 of the plate thickness from the surface (the region with a depth of 1 / 8 of the plate thickness from the surface to a depth of 3 / 8 of the plate thickness from the surface) and the center of the plate width direction is measured by electron backscatter diffraction at a measurement interval of 0.1 μm to obtain crystal orientation information. In the measurement, an EBSD analysis device consisting of a thermal field emission scanning electron microscope (JSM-7001F manufactured by JEOL) and an EBSD detector (DVC5 detector manufactured by TSL) is used. At this time, the vacuum degree in the EBSD analysis device is set to 9.6×10 -5 Pa or less, the acceleration voltage was set to 15 kV, the irradiation current level was set to 13, and the irradiation level of the electron beam was set to 62.
[0136] In addition, a backscattered electron image is taken in the same field of view. First, the grains in which ferrite and cementite are precipitated in layers are identified from the backscattered electron image, and the area fraction of the grains is calculated, thereby obtaining the area fraction of pearlite. Then, for grains other than the grains identified as pearlite, the "Grain Average Misorientation: Grain Average Orientation Difference" function of the software "OIM Analysis (registered trademark)" attached to the EBSD analysis device is used to analyze the obtained crystal orientation information, and the area with a Grain Average Misorientation value of less than 1.0° is identified as ferrite. The area fraction of ferrite is obtained by calculating the area fraction of the area identified as ferrite.
[0137] Next, in the remaining area (area where the Grain Average Misorientation value exceeds 1.0°), under the condition that the 5° grain boundary is defined as the grain boundary, when the maximum value of the "Grain Average IQ" of the ferrite area is set to Iα, the area exceeding Iα / 2 is extracted as bainite, and the area below Iα / 2 is extracted as "pearlite, martensite and tempered martensite". The area fraction of bainite is obtained by calculating the area ratio of the extracted bainite. In addition, the area fraction of pearlite obtained by the above-mentioned EBSD analysis is subtracted from the area fraction of the extracted "pearlite, martensite and tempered martensite" to obtain the total area ratio of martensite and tempered martensite.
[0138] (2-4) E value: 10.7 or more, I value: 1.020 or more
[0139] To suppress the occurrence of secondary shear planes, it is important to form a fracture surface after the shear plane is fully formed, and it is necessary to suppress the occurrence of cracks from the tool tip at an early stage during shearing. For this reason, it is important that the periodicity of the metal structure is low and the uniformity of the metal structure is high. In this embodiment, the occurrence of secondary shear planes can be suppressed by controlling the E (Entropy) value representing the periodicity of the metal structure and the I (Inverce differenced moment norm) value representing the uniformity of the metal structure.
[0140] The E value represents the periodicity of the metal structure. When the brightness is arranged periodically due to the formation of a banded structure, that is, when the periodicity of the metal structure is high, the E value decreases. In the present embodiment, since it is necessary to form a metal structure with low periodicity, it is necessary to increase the E value. If the E value is lower than 10.7, secondary shear surfaces are likely to occur. Starting from the periodically arranged structure, cracks occur from the tip of the shearing tool in the earliest stage of the shearing process, forming a fracture surface, and then a shear surface is formed again. From this, it is inferred that secondary shear surfaces are likely to occur. Therefore, the E value is set to be greater than 10.7, preferably greater than 10.8, and more preferably greater than 11.0. The higher the E value, the more preferred it is. There is no particular upper limit, and it can also be set to less than 13.0, less than 12.5, or less than 12.0.
[0141] The I value represents the uniformity of the metal structure. The larger the area of the region with a certain brightness, the higher the I value. The so-called high I value means that the uniformity of the metal structure is high. In the present embodiment, since it is necessary to form a metal structure with high uniformity, it is necessary to increase the I value. If the I value is lower than 1.020, due to the influence of the hardness distribution caused by the precipitates and the element concentration difference in the grains, cracks will occur from the tip of the shearing tool in the earliest stage of the shearing process, forming a fracture surface, and then forming a shear surface again. From this, it is inferred that a secondary shear surface is likely to occur. Therefore, the I value is set to be greater than 1.020, preferably greater than 1.025, and more preferably greater than 1.030. The higher the I value, the more preferred it is. There is no particular upper limit, and it can also be set to less than 1.200, less than 1.150, or less than 1.100.
[0142] The E value and I value can be obtained by the following method.
[0143] In this embodiment, the shooting area of the SEM image taken for calculating the E value and the I value is set to a position in the cross section parallel to the rolling direction, at a depth of 1 / 4 of the plate thickness from the surface of the steel plate (an area from 1 / 8 of the plate thickness to 3 / 8 of the plate thickness from the surface), and at the center of the plate width direction. In shooting the SEM image, a SU-6600 Schottky electron gun manufactured by Hitachi High-Technologies Corporation is used, the emitter is set to tungsten, and the acceleration voltage is set to 1.5 kV. Based on the above settings, the SEM image is output at a magnification of 1000 times and 256 levels of grayscale.
[0144] Next, the obtained SEM image was cut into 880×880 pixel areas, and the cut images were subjected to the smoothing process described in Non-Patent Document 3, with the contrast enhancement limit magnification set to 2.0 and the block size set to 8×8. The smoothed SEM image was rotated counterclockwise from 0 to 179 degrees at every degree except 90 degrees, and images were created at every degree, thereby obtaining a total of 179 images. Next, for each of these 179 images, the GLCM method described in Non-Patent Document 1 was used to collect the frequency values of the brightness between adjacent pixels in the form of rows and columns.
[0145] Let k be the rotation angle from the original image, and express the rows and columns of the 179 frequency values collected by the above method as p k (k = 0 to 89, 91 to 179). For each image, the generated p k After the sum is calculated, a 256×256 matrix P is normalized so that the sum of each component is 1. In addition, the E value and the I value are calculated using the following formula (1) and formula (2) described in Non-Patent Document 2, respectively. In the following formula (1) and formula (2), the value of the i-th row and j-th column of the matrix P is represented as P ij .
[0146] [Formula 1]
[0147]
[0148] [Formula 2]
[0149]
[0150] (2-5) Standard deviation of Mn concentration: 0.60 mass % or less
[0151] The standard deviation of the Mn concentration in the central position of the hot-rolled steel sheet involved in the present embodiment, which is 1 / 4 of the plate thickness from the surface and in the plate width direction, is 0.60% by mass or less. Thus, the hard phase can be evenly dispersed, and cracks can be prevented from occurring from the tip of the shearing tool in the earliest stage of shearing. As a result, the occurrence of secondary shear surfaces can be suppressed. The standard deviation of the Mn concentration is preferably 0.50% by mass or less, and more preferably 0.47% by mass or less. The lower limit of the standard deviation of the Mn concentration is preferably smaller from the viewpoint of suppressing excessive burrs, but due to the constraints of the manufacturing process, the actual lower limit is 0.10% by mass.
[0152] After the cross section (L section) of the hot-rolled steel plate parallel to the rolling direction is mirror-polished, the steel plate is measured at a depth of 1 / 4 of the plate thickness from the surface (the area from 1 / 8 of the plate thickness to 3 / 8 of the plate thickness from the surface) and the center position in the plate width direction by an electron probe microanalyzer (EPMA) to determine the standard deviation of the Mn concentration. The measurement conditions set the acceleration voltage to 15 kV, the magnification to 5000 times, and measure the distribution image in the range of 20 μm in the rolling direction of the sample and 20 μm in the plate thickness direction of the sample. More specifically, the measurement interval is set to 0.1 μm, and the Mn concentration is measured at more than 40,000 locations. Next, the standard deviation is calculated based on the Mn concentration obtained from the total measurement points, thereby obtaining the standard deviation of the Mn concentration.
[0153] (2-6) Average grain size of the surface layer: less than 3.0 μm
[0154] By refining the grain size of the surface layer, the inner cracks in the bend of the hot-rolled steel sheet can be suppressed. The higher the strength of the steel sheet, the easier it is for cracks to occur from the inside of the bend during the bending process (hereinafter referred to as inner cracks in the bend). The mechanism of the inner cracks in the bend is inferred to be as follows. Compressive stress is generated on the inside of the bend during the bending process. Initially, the entire inner side of the bend is uniformly deformed while the processing is progressing, but if the processing amount increases, the deformation cannot be borne by uniform deformation alone, and the deformation continues to progress due to the local concentration of strain (a shear deformation band occurs). The shear deformation band further grows and cracks occur and grow along the shear band from the inner surface of the bend. The reason why inner cracks in the bend are prone to occur with high strength is inferred to be because the uniform deformation is difficult to advance due to the decrease in work hardening energy associated with high strength, and deformation deviation is likely to occur, so a shear deformation band is generated in the early stage of processing (or under loose processing conditions).
[0155] According to the research of the present inventors, it is known that bending internal cracks become significant in steel plates with a tensile strength of 980MPa or above. In addition, the present inventors also found that the finer the grain size of the surface layer of the hot-rolled steel plate, the more the local strain concentration is suppressed, and the more difficult it is to cause bending internal cracks. In order to obtain the above-mentioned effect, it is preferred to set the average grain size of the surface layer of the hot-rolled steel plate to less than 3.0μm. Therefore, in this embodiment, the average grain size of the surface layer can also be set to less than 3.0μm. The average grain size of the surface layer is more preferably less than 2.5μm. The lower limit of the average grain size of the surface layer area is not particularly specified, and can also be set to 0.5μm.
[0156] In addition, the surface layer in the present embodiment refers to a region from the surface of the hot-rolled steel sheet to a position at a depth of 50 μm from the surface.
[0157] The grain size of the surface layer can be measured by EBSP-OIM (Electron Back Scatter Diffraction Pattern-Orientation Image Microscopy). The EBSP-OIM method is performed using a device that combines a scanning electron microscope and an EBSP analysis device and OIM Analysis (registered trademark) manufactured by AMETEK. The analyzable area of the EBSP-OIM method is the area that can be observed by SEM. Although it also depends on the resolution of the SEM, the EBSP-OIM method can be analyzed with a minimum resolution of 20nm.
[0158] In the cross section of the hot-rolled steel sheet parallel to the rolling direction, the area from the surface of the hot-rolled steel sheet to the position at a depth of 50 μm from the surface and the center position in the plate width direction, at a magnification of 1200 times, in the area of 40 μm×30 μm, at least 5 fields of view are analyzed, and the place where the angle difference between adjacent measurement points is 5° or more is defined as the grain boundary, and the area average grain size is calculated. The obtained area average grain size is taken as the average grain size of the surface layer.
[0159] 3. Tensile strength characteristics
[0160] The tensile strength characteristics (tensile strength, total elongation) of the mechanical properties of the hot-rolled steel sheet were evaluated in accordance with JIS Z2241: 2011. The test piece was the No. 5 test piece of JIS Z2241: 2011. The sampling position of the tensile test piece was defined as the portion 1 / 4 from the end in the width direction of the sheet, and the direction perpendicular to the rolling direction could be defined as the length direction.
[0161] The tensile (maximum) strength of the hot-rolled steel sheet involved in this embodiment is 980 MPa or more. Preferably, it is 1000 MPa or more. If the tensile strength is lower than 980 MPa, the applicable parts are limited and the contribution to the lightweighting of the vehicle body is small. There is no need to make a special upper limit, but from the perspective of suppressing die wear, it can also be set to 1780 MPa.
[0162] In addition, the total elongation is preferably set to 10.0% or more, and the product of the tensile strength and the total elongation (TS×El) is preferably set to 13000 MPa·% or more. The total elongation is more preferably set to 11.0% or more, and further preferably set to 13.0% or more. In addition, the product of the tensile strength and the total elongation is more preferably set to 14000 MPa·% or more, and further preferably set to 15000 MPa·% or more. By setting the total elongation to 10.0% or more and setting the product of the tensile strength and the total elongation to 13000 MPa·% or more, the applicable parts are not limited, which can greatly contribute to the lightweighting of the vehicle body.
[0163] 4.Plate thickness
[0164] The plate thickness of the hot-rolled steel plate involved in the present embodiment is not particularly limited, but can also be set to 1.2 to 8.0 mm. If the plate thickness of the hot-rolled steel plate is less than 1.2 mm, it is difficult to ensure the rolling end temperature, and the rolling load is too large, and hot rolling is sometimes difficult. Therefore, the plate thickness of the hot-rolled steel plate involved in the present embodiment can also be set to more than 1.2 mm. Preferably, it is more than 1.4 mm. On the other hand, if the plate thickness exceeds 8.0 mm, it is difficult to refine the metal structure, and sometimes it is difficult to obtain the above-mentioned metal structure. Therefore, the plate thickness can also be set to less than 8.0 mm, preferably less than 6.0 mm.
[0165] 5. Others
[0166] (5-1) Plating
[0167] The hot-rolled steel sheet with the above-mentioned chemical composition and metal structure involved in the present embodiment can also have a coating on the surface to form a surface-treated steel sheet for the purpose of improving corrosion resistance, etc. The coating can be an electroplated layer or a hot-dip coating. As the electroplated layer, electrogalvanizing, electroplating Zn-Ni alloy, etc. can be exemplified. As the hot-dip coating, hot-dip galvanizing, alloyed hot-dip galvanizing, hot-dip aluminum plating, hot-dip Zn-Al alloy plating, hot-dip Zn-Al-Mg alloy plating, hot-dip Zn-Al-Mg-Si alloy plating, etc. can be exemplified. The coating adhesion amount is not particularly limited and can be the same as before. In addition, by implementing appropriate chemical conversion treatment (such as coating and drying of chromium-free chemical conversion treatment liquid of silicate system) after plating, corrosion resistance can also be further improved.
[0168] 6. Manufacturing conditions
[0169] A suitable method for producing the hot-rolled steel sheet according to the present embodiment having the above-mentioned chemical composition and metal structure is as follows.
[0170] In order to obtain the hot-rolled steel sheet according to the present embodiment, an effective method is to heat the slab under predetermined conditions, perform hot rolling, accelerate cooling to a predetermined temperature range, and then perform slow cooling, thereby controlling the cooling process until coiling.
[0171] In a suitable method for manufacturing a hot-rolled steel sheet according to the present embodiment, the following steps (1) to (9) are performed in sequence. The slab temperature and the steel sheet temperature in the present embodiment refer to the slab surface temperature and the steel sheet surface temperature. In addition, the stress refers to the stress applied to the steel sheet in the rolling direction.
[0172] (1) After the slab is held in a temperature range of 700 to 850° C. for 900 seconds or more, it is heated again and held in a temperature range of 1100° C. or more for 6000 seconds or more.
[0173] (2) Hot rolling is performed in a temperature range of 850 to 1100° C. so that the plate thickness is reduced by 90% or more in total.
[0174] (3) After the rolling in the first stage before the final stage of hot rolling and before the final stage of rolling, a stress of 170 kPa or more is applied to the steel sheet.
[0175] (4) The hot rolling is completed so that the reduction ratio in the final stage of the hot rolling is set to 8% or more and the rolling end temperature Tf is set to 900°C or more and lower than 1010°C.
[0176] (5) After the final stage of hot rolling and before the steel sheet is cooled to 800° C., the stress applied to the steel sheet is set to less than 200 kPa.
[0177] (6) After the hot rolling is completed, the steel is cooled to a temperature range of 600 to 730°C at an average cooling rate of 50°C / second or more after cooling to a temperature range of 50°C or less at the hot rolling completion temperature Tf within 1 second after the hot rolling is completed. However, cooling to a temperature range of 50°C or less at the hot rolling completion temperature Tf within 1 second after the hot rolling is a more preferred cooling condition.
[0178] (7) In the temperature range of 600 to 730°C, slow cooling is performed at an average cooling rate of less than 5°C / s for 2.0 seconds or more.
[0179] (8) Cooling to a temperature range of 350°C or less at an average cooling rate of 50°C / s or more.
[0180] (9) Coiling is performed in a temperature range below 350°C.
[0181] By adopting the above-mentioned manufacturing method, a hot-rolled steel sheet having a metal structure excellent in strength, ductility and shear workability can be stably manufactured. That is, by appropriately controlling the slab heating conditions and hot rolling conditions, reducing the Mn segregation and isoaxing the austenite before the transformation, and combining it with the cooling conditions after hot rolling described later, a hot-rolled steel sheet having a desired metal structure can be stably manufactured.
[0182] (6-1) Slab, Slab Temperature and Holding Time during Hot Rolling
[0183] The slabs for hot rolling can be slabs obtained by continuous casting and slabs obtained by casting and slab opening, etc., and the slabs that have been hot-worked or cold-worked can be used as needed. The slabs for hot rolling are preferably kept in a temperature range of 700 to 850°C for more than 900 seconds when the slabs are heated, and then heated again and kept in a temperature range of 1100°C or more for more than 6000 seconds. Furthermore, when kept in a temperature range of 700 to 850°C, the temperature of the steel plate can be changed in the temperature range or set to be fixed. In addition, when kept at a temperature of more than 1100°C, the temperature of the steel plate can be changed in a temperature range of more than 1100°C or set to be fixed. In the austenite transformation in the temperature range of 700 to 850°C, Mn can be diffused along the ferrite region by distributing Mn between ferrite and austenite and extending its transformation time. As a result, the microscopic segregation of Mn that is unevenly present in the slab can be eliminated, and the standard deviation of the Mn concentration can be significantly reduced. Furthermore, by maintaining the slab in a temperature range of 1100° C. or higher for 6000 seconds or longer, the austenite grains can be made uniform during the slab heating.
[0184] Hot rolling is preferably performed by a reversing mill or a tandem mill as a multi-pass rolling. In particular, from the viewpoint of industrial productivity and the stress load on the steel sheet during rolling, it is more preferable to perform hot rolling by a tandem mill at least in the final two stages.
[0185] (6-2) Hot rolling reduction rate: The total plate thickness is reduced by more than 90% in the temperature range of 850-1100°C
[0186] By hot rolling in a manner that the plate thickness is reduced by more than 90% in the temperature range of 850 to 1100°C, the recrystallized austenite grains can be mainly refined, while promoting the accumulation of strain energy in the non-recrystallized austenite grains. In addition, while promoting the recrystallization of austenite, the atomic diffusion of Mn can also be promoted, reducing the standard deviation of the Mn concentration. Therefore, it is preferred to hot roll in a manner that the plate thickness is reduced by more than 90% in the temperature range of 850 to 1100°C.
[0187] Furthermore, the so-called plate thickness thinning in the temperature zone of 850 to 1100°C can be expressed by {(t0-t1) / t0}×100(%) when the entrance plate thickness before the initial rolling in the rolling in this temperature zone is set to t0 and the exit plate thickness after the final stage of rolling in this temperature zone is set to t1.
[0188] (6-3) Stress after the first stage of rolling before the final stage of hot rolling and before the final stage of rolling: 170 kPa or more
[0189] It is preferable to set the stress applied to the steel sheet after the rolling in the first stage before the final stage of hot rolling to 170 kPa or more. As a result, the {110} <001> The number of grains with the crystal orientation of {110} <001> It is a crystal orientation that is difficult to recrystallize, so by suppressing the formation of this crystal orientation, recrystallization based on the final stage of pressing can be effectively promoted. As a result, the banded structure of the hot-rolled steel sheet can be improved, the periodicity of the metal structure can be reduced, and the E value can be increased. When the stress applied to the steel sheet is less than 170 kPa, an E value of 10.7 or more cannot sometimes be achieved. The stress applied to the steel sheet is more preferably 190 kPa or more. The stress applied to the steel sheet can be controlled by adjusting the roller speed in the tandem rolling.
[0190] (6-4) Reduction ratio in the final stage of hot rolling: 8% or more, hot rolling end temperature Tf: 900°C or more and less than 1010°C
[0191] It is preferred to set the reduction rate in the final stage of hot rolling to 8% or more, and set the hot rolling end temperature Tf to 900°C or more. By setting the reduction rate in the final stage of hot rolling to 8% or more, the reduction in the final stage can be used to promote recrystallization. As a result, the banded structure of the hot-rolled steel sheet can be improved, the periodicity of the metal structure can be reduced, and the E value can be increased. By setting the hot rolling end temperature Tf to 900°C or more, the excessive increase in the number of ferrite nucleation sites in austenite can be suppressed. As a result, the formation of ferrite in the final structure (the metal structure of the hot-rolled steel sheet after manufacture) can be suppressed, and a high-strength hot-rolled steel sheet can be obtained. In addition, by setting Tf to less than 1010°C, the coarsening of the austenite grain size can be suppressed, and the E value can be set to 10.7 or more by reducing the periodicity of the metal structure.
[0192] (6-5) Stress after hot rolling in the final stage and until the steel plate is cooled to 800°C: less than 200 kPa
[0193] It is preferred that the stress applied to the steel plate after rolling in the final stage of hot rolling and until the steel plate is cooled to 800°C is set to less than 200 kPa. By setting the stress applied to the steel plate to less than 200 kPa, the recrystallization of austenite can be preferentially developed in the rolling direction, and the increase in the periodicity of the metal structure can be suppressed. As a result, the E value can be set to 10.7 or more. The stress applied to the steel plate is more preferably less than 180 MPa.
[0194] (6-6) After the hot rolling is completed, the hot rolling is cooled to a temperature range below the hot rolling end temperature Tf-50°C within 1 second, and then accelerated cooling is performed to a temperature range of 600 to 730°C at an average cooling rate of 50°C / second or more.
[0195] In order to suppress the growth of austenite grains refined by hot rolling, it is more preferable to cool by 50°C or more within 1 second after the hot rolling is completed. In order to cool to a temperature range below the hot rolling end temperature Tf-50°C within 1 second after the hot rolling is completed, it is sufficient to cool with a fast average cooling rate immediately after the hot rolling is completed, for example, by spraying cooling water on the steel plate surface. By cooling to a temperature range below Tf-50°C within 1 second after the hot rolling is completed, the grain size of the surface layer can be refined, and the bending internal crack resistance can be improved.
[0196] In addition, by accelerating cooling to a temperature range below 730°C at an average cooling rate of 50°C / second or more after the cooling, the formation of ferrite and pearlite with a small amount of precipitation strengthening can be suppressed. Thus, the strength of the hot-rolled steel sheet is improved. Furthermore, the average cooling rate mentioned here refers to the value obtained by dividing the temperature drop of the steel sheet from the start of accelerated cooling (when the steel sheet is introduced into the cooling device) to the end of accelerated cooling (when the steel sheet is exported from the cooling device) by the time required from the start of accelerated cooling to the end of accelerated cooling.
[0197] There is no particular upper limit on the cooling rate, but if the cooling rate is increased, the cooling equipment will be large-scale, which will increase the equipment cost. Therefore, considering the equipment cost, the cooling rate is preferably 300°C / second or less. In addition, it is best to set the cooling stop temperature of accelerated cooling to 600°C or more.
[0198] (6-7) In the temperature range of 600 to 730°C, slow cooling is performed with an average cooling rate of less than 5°C / s for more than 2.0 seconds.
[0199] By slow cooling at an average cooling rate of less than 5°C / s for more than 2.0 seconds in a temperature range of 600-730°C, precipitation-strengthened ferrite can be fully precipitated. Thus, the strength and ductility of the hot-rolled steel sheet can be taken into account. In addition, the average cooling rate here refers to the value obtained by dividing the temperature drop of the steel sheet from the cooling stop temperature of the accelerated cooling to the stop temperature of the slow cooling by the time required from the stop of the accelerated cooling to the stop of the slow cooling.
[0200] The time for slow cooling is preferably 3.0 seconds or more. The upper limit of the time for slow cooling is determined by the equipment layout, but it can be set to be approximately less than 10.0 seconds. In addition, there is no particular lower limit for the average cooling rate of slow cooling, but since it requires a large investment in equipment to heat it without cooling it, it can also be set to 0°C / s or more.
[0201] (6-8) Average cooling rate to coiling temperature: 50℃ / s or more
[0202] In order to suppress the area fraction of pearlite and obtain a tensile strength of 980 MPa or more, it is preferred to set the average cooling rate from the cooling stop temperature of slow cooling to the coiling temperature to 50°C / s or more. In this way, the parent phase structure can be hardened. In addition, the average cooling rate mentioned here refers to the value obtained by dividing the temperature drop of the steel plate from the cooling stop temperature of slow cooling with an average cooling rate of less than 5°C / s to the coiling temperature by the time required from the stop of slow cooling with an average cooling rate of less than 5°C / s to coiling.
[0203] (6-9) Coiling temperature: below 350℃
[0204] The coiling temperature is set to 350° C. or less. By setting the coiling temperature to 350° C. or less, the precipitation amount of iron carbides can be reduced, and the fluctuation of the hardness distribution in the hard phase can be reduced. As a result, the I value can be increased, and excellent shear workability can be obtained.
[0205] Example
[0206] Next, the effect of one solution of the present invention is described in more detail through an embodiment, but the conditions in the embodiment are an example of conditions adopted to confirm the feasibility and effect of the present invention, and the present invention is not limited to this one example of conditions. The present invention can adopt a variety of conditions within the scope of achieving the purpose of the present invention without departing from the gist of the present invention.
[0207] Steels having the chemical compositions shown in Tables 1 and 2 were melted, and slabs having a thickness of 240 to 300 mm were manufactured by continuous casting. The obtained slabs were used to obtain hot-rolled steel sheets shown in Tables 5A to 6B according to the manufacturing conditions shown in Tables 3A to 4B. Furthermore, the average cooling rate of slow cooling was set to less than 5°C / s. In addition, since the coiling temperature recorded in Tables 4A and 4B is 50°C as the lower limit of measurement, the actual coiling temperature of the steel recorded as 50°C is below 50°C.
[0208] The obtained hot-rolled steel sheets were subjected to the above-mentioned method to determine the area fraction of the metal structure, E value, I value, standard deviation of the Mn concentration, average grain size of the surface layer, tensile strength TS and total elongation El. The obtained measurement results are shown in Tables 5A to 6B.
[0209] Furthermore, the remainder of the structure is one or two or more of bainite, martensite and tempered martensite.
[0210] Evaluation method of characteristics of hot-rolled steel sheets
[0211] (1) Tensile strength characteristics
[0212] When the tensile strength TS is 980 MPa or more, the total elongation El is 10.0% or more, and the tensile strength TS×total elongation El is 13000 MPa·% or more, the hot-rolled steel sheet is judged as qualified as having excellent strength and ductility. If any of these conditions is not met, the hot-rolled steel sheet is judged as not having excellent strength and ductility.
[0213] (2) Shear processability
[0214] The shear workability of the hot-rolled steel sheet was evaluated by punching test. Three punching holes were made for each example with a hole diameter of 10 mm, a clearance of 10%, and a punching speed of 3 m / s. Then, the cross-section of the punching hole at right angles to the rolling direction and the cross-section parallel to the rolling direction were buried in resin, and the cross-sectional shape was photographed with a scanning electron microscope. In the obtained observation photograph, it can be observed Figure 1 or Figure 2 Furthermore, Figure 1 is an example of the sheared end surface of the hot-rolled steel sheet according to the present invention. Figure 2 This is an example of a sheared end surface of a hot-rolled steel sheet according to a comparative example. Figure 1 In the figure, it is the shear end surface of collapsed edge - shear surface - fracture surface - burr. On the other hand, Figure 2In the figure, it is a shear end surface of collapsed edge - shear surface - fracture surface - shear surface - fracture surface - burr. Here, the collapsed edge is the area of the R-shaped smooth surface, the shear surface is the area of the punched end surface separated by shear deformation, the fracture surface is the area of the punched end surface separated by cracks generated near the blade tip, and the burr is the surface with a protrusion protruding from the bottom of the hot-rolled steel plate.
[0215] In the obtained shear end faces, in the two faces perpendicular to the rolling direction and the two faces parallel to the rolling direction, for example, Figure 2 In the case of the shear plane-fracture plane-shear plane shown in the figure, it is judged that a secondary shear plane is formed. Four surfaces of each punching are observed, and a total of 12 surfaces are observed. If no surface has a secondary shear plane exposed, it is judged to be qualified as a hot-rolled steel sheet with excellent shear workability, and it is recorded as "no" in Table 6A and Table 6B. On the other hand, if even one secondary shear plane is formed, it is judged to be unqualified as a hot-rolled steel sheet with poor shear workability, and it is recorded as "yes" in Table 6A and Table 6B.
[0216] (3) Resistance to bending cracks
[0217] The bending internal crack resistance was evaluated by the following bending test.
[0218] A 100mm×30mm rectangular test piece was cut out from the 1 / 2 position in the width direction of the hot-rolled steel plate to obtain a bending test piece. The bending in which the bending ridgeline is parallel to the rolling direction (L direction) (L-axis bending) and the bending in which the bending ridgeline is parallel to the direction perpendicular to the rolling direction (C direction) (C-axis bending) were investigated for the bending internal crack resistance according to IS Z2248:2014 (V-block 90° bending test) to find the minimum bending radius without cracking. The average value of the minimum bending radius of the L axis and the C axis was divided by the plate thickness, and the value obtained as the limit bending R / t was set as the index value of the bending internal crack resistance. When R / t is 2.5 or less, it is judged to be a hot-rolled steel plate with excellent bending internal crack resistance.
[0219] However, regarding the presence or absence of cracks, the test piece after the V-block 90° bending test was cut along a surface parallel to the bending direction and perpendicular to the plate surface, and after the cut surface was mirror-polished, cracks were observed under an optical microscope. When the length of the crack observed on the inner side of the bend of the test piece exceeded 30 μm, it was judged that cracks were present.
[0220] The obtained results are shown in Table 6A and Table 6B.
[0221]
[0222]
[0223] Table 3A
[0224]
[0225] Underlined text indicates that the manufacturing conditions were not preferred.
[0226] Table 3B
[0227]
[0228] Underlined text indicates that the manufacturing conditions were not preferred.
[0229] Table 4A
[0230]
[0231] Underlined text indicates that the manufacturing conditions were not preferred.
[0232] Table 4B
[0233]
[0234] Underlined text indicates that the manufacturing conditions were not preferred.
[0235] Table 5A
[0236]
[0237] Underlined elements indicate properties that are outside the scope of the present invention or are not preferred.
[0238] Table 5B
[0239]
[0240] Underlined elements indicate properties that are outside the scope of the present invention or are not preferred.
[0241] Table 6A
[0242]
[0243] Underlined elements indicate properties that are outside the scope of the present invention or are not preferred.
[0244] Table 6B
[0245]
[0246] Underlined elements indicate properties that are outside the scope of the present invention or are not preferred.
[0247] From Tables 5A to 6B, it is known that the hot-rolled steel sheets of the examples of the present invention have excellent strength, ductility and shear workability. In addition, it is known that in the examples of the present invention, the hot-rolled steel sheets with an average grain size of the surface layer of less than 3.0 μm have the above-mentioned properties and also have excellent resistance to bending internal cracking.
[0248] On the other hand, it was found that the hot-rolled steel sheets according to the comparative examples did not have any one or more of excellent strength, ductility, and shear workability.
[0249] Industrial Applicability
[0250] According to the above embodiment of the present invention, a hot rolled steel sheet having excellent strength, ductility and shear workability can be provided. In addition, according to the above preferred embodiment of the present invention, a hot rolled steel sheet having the above characteristics and excellent bending internal crack resistance can be obtained while suppressing the occurrence of bending internal cracks.
[0251] The hot-rolled steel sheet of the present invention is suitable as an industrial raw material for automobile components, mechanical structural parts and building components.
Claims
1. A hot rolled steel plate, characterized in that: The chemical composition is expressed in mass % as follows: C:0.050~0.250%、 Si: 0.05-3.00%, Mn: 1.00~4.00%, One or more of Ti, Nb and V: 0.060 to 0.500% in total, Sol.Al: 0.001~2.000%, P: 0.100% or less, S: 0.0300% or less, N: 0.1000% or less, O: 0.0100% or less, Cu: 0-2.00%, Cr:0~2.00%、 Mo: 0-1.00%, Ni: 0-2.00%, B:0~0.0100%、 Ca: 0~0.0200%, Mg: 0~0.0200%, REM: 0~0.1000%、 Bi: 0~0.020%, One or more of Zr, Co, Zn and W: 0 to 1.00% in total, and Sn: 0~0.05%, The remainder is Fe and impurities; The metal structure contains in area %: The retained austenite is less than 3.0%, the ferrite is 15.0% or more and less than 60.0%, and the pearlite is less than 5.0%; The E value representing the periodicity of the metal structure is greater than 10.7, and the I value representing the uniformity of the metal structure is greater than 1.020; The standard deviation of the Mn concentration is 0.60 mass % or less; Tensile strength is above 980MPa; In the measurement of the E value and the I value, the photographing area of the SEM image taken to calculate the E value and the I value was set to a depth position of 1 / 4 of the plate thickness from the surface of the steel plate in a cross section parallel to the rolling direction. In the measurement of the standard deviation of Mn concentration, after the L-section of the hot-rolled steel sheet parallel to the rolling direction was mirror-polished, the standard deviation of Mn concentration was measured by EPMA at a depth of 1 / 4 of the sheet thickness from the surface and at the center position in the sheet width direction.
2. The hot rolled steel sheet according to claim 1, characterized in that: The average crystal grain size of the surface layer is less than 3.0 μm.
3. The hot rolled steel sheet according to claim 1 or 2, characterized in that: The chemical composition, in mass%, contains one or more elements selected from the following: Cu: 0.01-2.00%, Cr:0.01~2.00%、 Mo: 0.01~1.00%, Ni: 0.02-2.00%, B:0.0001~0.0100%、 Ca: 0.0005~0.0200%, Mg: 0.0005~0.0200%, REM: 0.0005~0.1000%, and Bi: 0.0005~0.020%.
Citation Information
Patent Citations
Cold rolled steel sheet excellent in blanking property and its production
JP1998168544A
High strength automobile steel plate superior in collision safety and formability, and its manufacture
JP1999061326A
High strength steel sheet having excellent elongation and stretch-flange formability
JP2005179703A
High strength hot rolled steel sheet having excellent stamping workability and its production method
JP2005298924A
Manufacturing method of tank
JP2020143742A